2015
DOI: 10.1002/jsfa.7284
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effect of water extracts of Graptopetalum paraguayense supplementation in subjects with metabolic syndrome: a preliminary study

Abstract: This study demonstrated a significant reduction in inflammatory status in MS after WGP supplementation. WGP may exert an anti-inflammatory effect on MS in addition to its antioxidant ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As early as ancient China GP was traditionally used to treat a number of diseases: modulating blood pressure, relieving liver disease, relieving pain and infections, detoxification. Reported biological effects of GP include tyrosinase inhibition (Huang et al 2005), antioxidants (Chao et al 2019), regulation of hypertension (Chen et al 2007;Chung et al 2009), hepatoprotective effect (Duh et al 2011;Hsu et al 2019), antitumor activity (Ai et al 2017), anti-inflammatory (Chen et al 2016) and Alzheimer's disease therapy (Wu et al 2019). There are no data in the literature on the antiviral activity (including anti-herpes activity) of GP.…”
Section: Introductionmentioning
confidence: 99%
“…As early as ancient China GP was traditionally used to treat a number of diseases: modulating blood pressure, relieving liver disease, relieving pain and infections, detoxification. Reported biological effects of GP include tyrosinase inhibition (Huang et al 2005), antioxidants (Chao et al 2019), regulation of hypertension (Chen et al 2007;Chung et al 2009), hepatoprotective effect (Duh et al 2011;Hsu et al 2019), antitumor activity (Ai et al 2017), anti-inflammatory (Chen et al 2016) and Alzheimer's disease therapy (Wu et al 2019). There are no data in the literature on the antiviral activity (including anti-herpes activity) of GP.…”
Section: Introductionmentioning
confidence: 99%
“…As early as ancient China GP was traditionally used to treat a number of diseases: modulating blood pressure, relieving liver disease, relieving pain and infections, detoxification. Reported biological effects of GP include tyrosinase inhibition [13], antioxidants [14], regulation of hypertension [15,16], hepatoprotective effect [17,18], antitumor activity [19], anti-inflammatory [20] and Alzheimer's disease therapy [21]. There are no data in the literature on the antiviral activity (including anti-herpes activity) of GP.…”
Section: Introductionmentioning
confidence: 99%
“…Graptopetalum paraguayense E. Walther (GP) belongs to the Crassulaceae family and is a succulent plant species distributed in tropical and subtropical countries and grown mainly as an ornamental house plant in temperate regions. It was found that GP aqueous extracts show anti-inflammatory [14], antioxidant [15] and antineoplastic activities [16]. Preliminary phytochemical studies on the effect of n-butanol extract from fresh watery juice of GP leaves demonstrate anticonjunctivitis activity due to probable synergistic effect between alkylamines, hydroxycarboxylic, aliphatic and aromatic carboxylic acids [17].…”
Section: Introductionmentioning
confidence: 99%